SPIRAL CT SCAN OF THE THYMIC CYST - PEKANAN, Patchrin; SUCHATO, Chirote; CHOTESKULRAT, Vibul; PANJAPIYAKUL, Chingyium; SUWANWILAI, Charoen (The ASEAN Journal of Radiology, 2023)
A case of uncomplicated thymic cyst was demonstrated by plain films and spiral CT scan. The patient was 58 years old, having chronic cough. Images of simple cyst at anterior mediastinum extending to left perihilar area were shown.